The Modelling and Simulation of Bipolar Hybrid Stepping Motor by Matlab/Simulink. (2015) - Morar, Alexandru
Abstract: Development of digital electronics and microcontroller systems has led to development of electrical motors capable to tee digitally controlled. These motors are widely known as stepper motors and the enable transformation of pulsed electrical excitation into mechanical energy. Matlab/Simulink is used as a simulation tool for bipolar stepper motor enabling motor transient characteristics of current, voltage, torque and speed to be obtained. Different operating motor regimes are simulated as no-load and rated load operation. Te obtained results are in good accordance with the theoretical expectation and with the results of analytical computations. Adequate conclusions regarding motor performance characteristics are derived.